Lactate – food component, oncometabolite or master regulator of cellular metabolism - Zakłos-Szyda, Małgorzata; Koziołkiewicz, Maria (Lodz University of Technology Press, 2025)
Lactate, initially identified in the context of yogurt fermentation and considered merely a metabolic byproduct, is now recognized as a pivotal regulator of cellular metabolism and signaling. It accumulates during exercise, cancer and inflammation, influencing physiological, and pathological processes. Lactate exerts effects through specific transporters and G-protein-coupled receptors such as GPR81 and GPR132, modulating metabolic reprogramming and immune responses. Additionally, lactate mediates post-translational modifications via histone and non-histone lactylation, impacting gene expression and protein function. Here we review recent advances elucidating lactate’s multifaceted roles, including its transport mechanisms, receptor-mediated signaling and lactylation pathways, highlighting their contributions to metabolism, tumor progression, immune regulation and gut homeostasis. Understanding these mechanisms reveals lactate as a master regulator with therapeutic potential in metabolic, inflammatory and oncological diseases. Further research into lactate-specific receptors and lactylation enzymes may enable targeted interventions to modulate lactate-driven pathways for clinical benefit.
Keywords: lactate metabolism; lactylation; GPR81 receptor; monocarboxylate transporters (MCTs); histone modification; metabolizm mleczanu; laktylacja; receptor GPR81; transportery monokarboksylanów (MCT); modyfikacja histonów